Voltammetric Determination of Nickel in Chocolate by Differential Pulse Cathodic Stripping Analysis - Mohammad Zairy Azren, Jainal@ Zainal (PPSP, Universiti Sains Malaysia, 2007)
The determination of nickel in the chocolate was performed by Differential Pulse Cathodic Stripping Analysis(DPCSV). Chocolate was a complex sample with a high content of organic compounds such as sugar, protein, fat, lecithin and many more and its analysis generally involves digestion procedures that might include the risk of losses and/or contamination. Wet digestion by using concentrated nitric acid and 1:1 ratio of distilled water-hydrochloric acid on the sample was selected on this study because of its availability and low cost . Sample was then processed to the sample analysis stage. Prior to the sample analysis by DPCSV, the optimum pH for the supporting electrolyte, Britton-Robinson Buffer (BRB}, 0.04 M and optimum parameters for the analysis was determined. Optimum pH for the supporting electrolyte, BRB was pH 4. Initial potential, Ei of -0.68 V, final potential, Er of-1.15 V, scan rate of0.050 V/s, deposition potential of -1.4 V, equilibration time of 5 s and deposition time, tacc of 20 s were the optimized parameters used in this study. The validation of methodology was performed by plotting a calibration curve peak height, ip versus different concentrations of nickel (5 ppm) as the stock solution. A linear graph with the regression equation of Y= 0.820+ 23.322X, correlation coefficient of 0.966, standard deviation of 1.129, sensitivity of 23.322 nA/ppm and limit of detection of 0.145 ppm was obtained. 3 different brands of chocolate were analyzed. The results in all samples show absence of nickel.